Microsatellite loci in two epiphytic lichens with contrasting dispersal modes: Nephroma laevigatum and N. parile (Nephromataceae)1. (3rd November 2014) - Belinchón, Rocío; Ellis, Christopher J.; Yahr, Rebecca
Abstract : Premise of the study: Microsatellite markers were characterized for two epiphytic cyanolichens, Nephroma laevigatum and N. parile (Nephromataceae), and will be used to investigate population structure and estimate gene flow among populations of these two closely related species with contrasting dispersal modes. Methods and Results: Twelve and 14 microsatellite loci were characterized for N. laevigatum and N. parile, respectively. Allele number in N. laevigatum ranged from three to 13 per locus, while in N. parile there were from two to six alleles per locus. As expected, the sexually reproducing N. laevigatum had higher genetic diversity than the predominantly asexual N. parile . Conclusions: This new set of markers is suitable for studying population structure and providing insights into gene flow among populations and for understanding processes of diversification. Compared between the species, they will facilitate an understanding of the influence of contrasting reproductive strategies on population and community structure.